STRATEGIES TO ENHANCE DECISION MAKING AND DESIGN THINKING SKILLS FOR INDUSTRIAL DESIGN STUDENTS - Budhyani, I Dewa Ayu Made; Widiastini, Ni Wayan Eka; Puger, I Gusti Ngurah; Yudiana, I Kadek Edi (LPPM Universitas Jambi, 2025)
The low levels of decision-making skills (DMS) and design thinking skills (DTS) among Industrial Design Engineering students in Bali hinder their readiness to meet industry demands. This problem is compounded by students’ low self-efficacy in making career decisions and their limited exposure to authentic, collaborative, and interdisciplinary training. This study aims to address these gaps by implementing and evaluating a transformative multicultural education model as an innovative strategy to enhance DMS and DTS. Employing an experimental research design, the study involved 64 vocational schools (SMK) across Bali, selected to represent diverse cultural and socio-economic contexts. Data were collected through validated structured questionnaires measuring DMS and DTS, followed by quantitative analysis using descriptive statistics and MANOVA. The findings reveal that the transformative multicultural learning model produced a statistically significant improvement in both skill domains, fostering not only technical creativity but also culturally responsive decision-making. The novelty of this research lies in its integration of multicultural perspectives directly into the design thinking framework—positioning cultural diversity as an active driver of creative problem-solving rather than a passive background element. Furthermore, the approach embeds real-world project simulations grounded in local cultural values, bridging the gap between academic preparation and industry expectations. This combination of cultural adaptation, critical thinking, and collaborative design creates a robust foundation for inclusive, future-ready learning environments. The results suggest that transformative multicultural education can serve as a scalable, culturally relevant model for preparing students to navigate complex, globalized work environments while retaining local identity.